Influence of the Nd:YAG Laser Pulse Duration on the Temperature of Primary Enamel - R. A. Valério; V. S. da Cunha; R. Galo; F. A. de Lima; L. Bachmann; S. A. M. Corona; M. C. Borsatto (The Scientific World Journal, 2015)
The aim of this study is to evaluate the temperature change on specimens of primary enamel irradiated with different pulse duration of Nd:YAG laser. Fifteen sound primary molars were sectioned mesiodistally, resulting in 30 specimens (3.5 × 3.5 × 2.0 mm). Two small holes were made on the dentin surface in which K-type thermocouples were installed to evaluate thermal changes. Specimens were randomly assigned in 3 groups (n=10): A = EL (extra long pulse, 10.000 μs), B = LP (long pulse, 700 μs), and C = SP (short pulse, 350 μs). Nd:YAG laser (λ = 1.064 μm) was applied at contact mode (10 Hz, 0.8 W, 80 mJ) and energy density of 0.637 mJ/mm2. Analysis of variance (ANOVA) was performed for the statistical analysis (P=0.46). Nd:YAG laser pulse duration provided no difference on the temperature changes on primary enamel, in which the following means were observed: A = EL (23.15°C ± 7.75), B = LP (27.33°C ± 11.32), and C = SP (26.91°C ± 12.85). It can be concluded that the duration of the laser pulse Nd:YAG increased the temperature of the primary enamel but was not influenced by different pulse durations used in the irradiation.